Air-powder polishing on self-ligating brackets after clinical use: effects on debris levels - ARAGÓN, Mônica Lídia Castro de (Universidade Federal do Pará, 2017)
Introduction: Debris buildup on brackets and arch surfaces is one of the main factors that can influence the intensity of friction between bracket and orthodontic wire. Objective: This study sought to evaluate the effect of air-powder polishing cleaning on debris levels of self-ligating ceramic brackets at the end of orthodontic treatment, compared to the behavior of conventional brackets. Methods: Debris levels were evaluated in metal conventional orthodontic brackets (n = 42) and ceramic self-ligating brackets (n = 42) on canines and premolars, arranged in pairs. There were brackets with and without air-powder polishing. At the end of orthodontic treatment, a hemiarch served as control and the contralateral hemiarch underwent prophylaxis with air-powder polishing. Debris buildup in bracket slots was assessed through images, and Wilcoxon test was used to analyze the results. Results: The median debris levels were statistically lower in the conventional metal brackets compared to self-ligating ones (p = 0.02), regarding brackets not submitted to air-powder polishing. Polishing significantly reduced debris buildup to zero in both systems, without differences between groups. Conclusions: Ceramic self-ligating brackets have a higher debris buildup in comparison to conventional metal brackets in vivo, but prophylaxis with sodium bicarbonate jet was effective in reducing debris levels in self-ligating and also in conventional brackets.